A Metacognitive Perspective of Visual Working Memory With Rich Complex Objects - Sahar, Tomer; Sidi, Yael; Makovski, Tal (Frontiers in Psychology, 2020)
Visual working memory (VWM) has been extensively studied in the context of memory capacity. However, less research has been devoted to the metacognitive processes involved in VWM. Most metacognitive studies of VWM studies tested simple, impoverished stimuli, whereas outside of the laboratory setting we typically interact with meaningful, complex objects. Thus, the present study aimed to explore the extent to which people are able to monitor VWM of real-world objects that are more ecologically valid and further afford less inter-trial interference. Specifically, in three experiments, participants viewed a set of either four or six memory items, consisting of images of unique real-world objects that were not repeated throughout the experiment. Following the memory array, participants were asked to indicate where the probe item appeared (Experiment 1) whether it appeared at all (Experiment 2) or whether it appeared and what was its temporal order (Experiment 3). VWM monitoring was assessed by subjective confidence judgments regarding participants’ objective performance. Similar to common metacognitive findings in other domains, we found that subjective judgments over-estimated performance and under-estimated errors, even for real-world, complex items held in VWM. These biases seem not to be task-specific as they were found in temporal, spatial and identity VWM tasks. Yet, the results further showed that meaningful, real-world objects were better remembered than distorted items, and this memory advantage also translated to metacognitive measures.